(untitled) (UNIZIK Journal of STM Education, 2023)
The study investigated social intelligence and self-efficacy as correlates of academic achievement in Mathematics among secondary school students in Abia State, Nigeria. The study adopted a correlational research design. Three research questions were raised and three 2hypotheses were formulated at 0.05 level of significance to guide the study. The population of the study comprised 3,287 SS1 students drawn from 248 public senior secondary schools in the seventeen (17) Local Government Areas (L.G.As) encompassing the three education zones that make up Abia State. A sample size of 357 students was selected from the population using accidental sampling technique. One researcher developed instrument titled “Social Intelligence and Self -Efficacy Scale” (SISES) was used together with the continuous assessment “Mathematics Test Scores” (MTS) of the students to carry out this study. The instruments were validated by experts in Measurement and Evaluation and Mathematics. The instrument had reliability coefficient of 0.87 determined using test re-test method. The collected data was analyzed using Pearson’s product moment correlation. The result of the study revealed that: self-regulation, selfawareness and mastery of experience all had high positive relationship with academic achievement in Mathematics. The researcher made some recommendations among which were that; Self regulation techniques such as self punishment, self instruction, self monitoring, thought stopping technique and turtle technique should be by students improve their self regulation as it has far reaching positive relationship with their academic achievement in Mathematics.